A COMPREHENSIVE STUDY ON ACADEMIC ANXIETY OF SECONDARY SCHOOL STUDENTS IN UKHRUL DISTRICT, MANIPUR - Devi, Laiphrakpam Nirmala; Shimray, Ronra Chonreiphy; Devi, Ahanthem Bachandari (International Journal of Research -GRANTHAALAYAH, 2025)
The present study provides a comprehensive understanding of academic anxiety among secondary school students in the Ukhrul District of Manipur. The objective of the study was to determine the level of academic anxiety among higher secondary school students in Ukhrul District, Manipur, based on their gender, type of school, and stream differences. The investigator employed a Descriptive Survey method. The study population consisted of students in classes XI and XII from the Ukhrul District, Manipur, under the Council of Higher Secondary Education, Manipur (COHSEM). The study sample consisted of 400 students, selected using Simple Random sampling. The Academic Anxiety Scale (AAS, 2017) was developed by M. Abid Siddiqui and Atieq Ul Rehman. A standardised questionnaire to measure the academic anxiety among higher secondary school students. The present study employed descriptive and inferential statistics, including percentages and the t-test, for comparison between groups. The findings reveal that the majority of secondary students experience an average level of academic anxiety. No significant differences were observed across gender, type of school, and stream.